Senandung Syair Buayan Bayi Bagi Masyarakat Melayu Riau Perspektif Hukum Islam (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
The tradition of the poetry of baby crocodiles is part of a dynamic culture that can strengthen the cultural position of the Malay people. However, humming and poetry in Islam is seen by some groups who take issue with it because poetry is something that is created without proof, it can alienate and neglect Muslims from worshiping Allah SWT. The form of research carried out is library research using a descriptive narrative approach by analyzing conceptually and examining the relationship between concepts in a text. To obtain novelty, researchers need to analyze the data presentation through content analysis and the data obtained is presented in the form of descriptive analysis. The Islamic legal perspective of singing baby crocodile poetry can be understood that the law can be permissible when the poetry used has no prohibitions and no commands, but the law can change to Sunnah when the poetry text is replaced in the form of besholawat, dhikr and other tayibah sentences, but the law can also change. The perspective of Islamic law becomes makruh when the poetry text is something that is unethical according to Islamic law and applicable norms.